A repertoire of cationic and anionic conductances at the plasma membrane of Medicago truncatula root hairs. (12th March 2019) - Wang, Limin; Guo, Man‐Yuan; Thibaud, Jean‐Baptiste; Véry, Anne‐Aliénor; Sentenac, Hervé
Summary: Root hairs, as lateral extensions of epidermal cells, provide large absorptive surfaces to the root and are major actors in plant hydromineral nutrition. In contact with the soil they also constitute a site of interactions between the plant and rhizospheric microorganisms. In legumes, initiation of symbiotic interactions with N2 ‐fixing rhizobia is often triggered at the root hair cell membrane in response to nodulation factors secreted by rhizobia, and involves early signaling events with changes in H +, Ca 2+, K + and Cl − fluxes inducing transient depolarization of the cell membrane. Here, we aimed to build a functional repertoire of the major root hair conductances to cations and anions in the sequenced legume model Medicago truncatula . Five root hair conductances were characterized through patch‐clamp experiments on enzymatically recovered root hair protoplasts. These conductances displayed varying properties of voltage dependence, kinetics and ion selectivity. They consisted of hyperpolarization‐ and depolarization‐activated conductances for K +, cations or Cl − . Among these, one weakly outwardly rectifying cationic conductance and one hyperpolarization‐activated slowly inactivating anionic conductance were not known as active in root hairs. All five conductances were detected in apical regions of young growing root hairs using membrane spheroplasts obtained by laser‐assisted cell‐wall microdissection. Combined with recent root hair transcriptomes of M. truncatula, this functional repertoire of conductances is expected to help the identification of candidate genes for reverse genetics studies to investigate the possible role of each conductance in root hair growth and interaction with the biotic and abiotic environment. Significance Statement: Five plasma membrane root hair conductances to cations and anions, potentially involved in plant nutrition, early nodulation factor signaling or root hair development, are functionally characterized in the model legume Medicago truncatula . Two of them have no reported counterparts in root hairs from other plant species. Together, they constitute the most documented functional repertoire of transport systems in root hairs, which could be combined with existing transcriptomes for future elucidation of their physiological function.